Verbal hostility, corporal punishment, nonreasoning strategies, and directiveness in reflecting authoritarian parenting style - Pipih Muhopilah; Fatwa Tentama (University of Muhammadiyah Malang, 2022)
Parenting is classified into several types, one of which is authoritarian parenting. Verbal hostility, corporal punishment, nonreasoning / punitive strategies, and directiveness are characteristics of this parenting style. The construct validity and construct reliability of the authoritarian parenting scale, as well as the characteristics and indicators that reflect authoritarian parenting, are being investigated. This study included all students in class VIII at Yogyakarta’s state junior high schools X, Y, and Z, which totaled 524 students. This study’s sample size was 185 students. The sampling technique employs cluster random sampling. Data is gathered using an authoritarian parenting scale. The research instruments are distributed directly to the subject. Structural Equation Modeling (SEM) was used to analyze the research data in the SmartPLS 3.2.8 program. The data analysis results of this study show that the characteristics and indicators that reflect authoritarian parenting are valid and reliable. The most dominant aspect that reflects authoritarian parenting is corporal punishment, while directiveness is the weakest aspect that reflects authoritarian parenting. As a result, because the theory describing the construct of authoritarian parenting corresponds to empirical data obtained from the subject, the measurement model can be accepted.